Effectiveness of netting in decreasing fruit surface temperature and sunburn damage of red-blushed pear - Goodwin, Ian; McClymont, Lexie; Turpin, Susanna; Darbyshire, Rebecca (New Zealand journal of crop and horticultural science, 2018)
Pear fruit are subject to sun damage from high fruit surface temperature (FST). Shade netting has been shown to decrease FST and sunburn damage of apples but also decreased fruit colour. The aim of this study was to investigate the effects of netting on FST, fruit sunburn and fruit colour of the red-blushed pear cultivar 'ANP-0131'. FST was measured using fine-wire thermocouples inserted into 54 fruit in a netted block of trees and into 56 fruit in adjoining rows of non-netted trees. Netting reduced the maximum FST by 10%. FST under netting did not exceed the reported sunburn damage threshold of 47°C despite air temperature reaching 38.6°C. The maximum FST in the non-netted site regularly exceeded the sunburn damage threshold and reached a maximum of 50.3°C. Assessments of sunburn damage showed a clear decrease in sunburn (amount and severity) for fruit from the netted trees; however, netting negatively affected colour intensity and coverage.